Characteristics of the Location of Forage Crops at Dairy Cattle Backyard Farming in Banyumas Regency - Hendarto, E; Suwarno, Suwarno (ANIMAL PRODUCTION, 2013)
One of the supports of the dairy farm productivity is forage crops whose existence is a major factor. Location as a land use pattern has many characteristics in line with situation. The purpose of this study was to describe the characteristics of area locations of forage crops at backyard dairy farms in Banyumas Regency. The method of this research was a survey with qualitative approach as a model of naturalistic paradigm. Â Phenomenological research was impelemented in this study. The research sites were on 5 (five) developing sub-districts of backyard dairy farm locations. The results showed that the pattern of land use for the forage plant source in backyard dairy cattle farm in Banyumas Regency in each district area was is affected by the parameters of different landscapes of land ownership. Based on the results it can be concluded that the characteristics of the pastures ware flat land, sloping and undulating topography, that were located near the rice fields, roads and yards. The location of the forage crops included the use of wet and dry land, and the combination of them, in monoculture and mixed cropping with other crops, not only on lands owned by farmers themselves, but also the uses of land owned by their families.Â Animal Production 15(2):89-97, May 2013